Performance Analysis Of Professional Basketball League Players - Agnesa Aulia Sutrisno; Yudy Hendrayana; Nuryadi (Journal of Multidisciplinary Science, 2022)
The most successful teams are teams that can play efficiently and perform well. Performance is essential in sports, whether individual or group because all players with good performance will bring their team as winners. This study aimed to determine the performance of players who participated in the Indonesian Basketball League. The research method used is a descriptive correlation. The study was conducted on all teams participating in the 2017 Indonesian Basketball League. The instrument used to measure performance uses software from Fibalivestats. All data were processed using SPSS 20 for windows. The results of data processing show that the results of calculating the effectiveness of players who have excellent effectiveness from all games with a total of 182 from the Pelita Jaya team, the results of the calculation of effectiveness are based on positions which are divided into five positions, Point Guard positions total effectiveness 149 from the Jakarta Aspac team, Shotting Guard positions The total effectiveness of the Pelita Jaya team is 156, the Small Forward position has a total effectiveness of 176 from the Satria Muda team, the Power Forward position has total effectiveness of 116 from the Aspac Jakarta team. The Center position has total effectiveness of 182 from Pelita Jaya. The result of the highest team efficiency is the Pelita Jaya Jakarta team, with a total efficiency of 1218 and 1330 points. The results of this study show a significant relationship between player performance and team achievement.